Current status of proximal gastrectomy for gastric and esophagogastric junctional cancer: A review. Issue 5 (21st June 2020) - Nunobe, Souya; Ida, Satoshi
Abstract: Proximal gastrectomy (PG) is one of the function‐preserving surgical methods for the treatment of upper gastric cancer. Favorable postoperative results have been reported in comparison with total gastrectomy. However, because there are challenges, such as postoperative reflux esophagitis, anastomotic stenosis, and residual food, appropriate selection of a reconstruction method is crucial. Some methods include esophagogastric anastomosis, including simple esophagogastrostomy, tube‐like stomach esophagogastrostomy, side overlap with fundoplication by Yamashita, and double‐flap technique, and reconstruction using the small intestine, including double‐tract methods, jejunal interposition, and jejunal pouch interposition. However, standard reconstruction methods are yet to be established. PG has also been employed in early gastric cancer of the upper third of the stomach, and indications have also been extended to esophagogastric junction cancer, which has shown an increase in recent years. Although many retrospective studies have revealed the functional benefits or oncological safety of PG, the characteristics of each surgical procedure should be understood so that an appropriate reconstruction method, with a reflux prevention mechanism and minimal postoperative injury, can be selected.